Acute heat stress detrimental effects transpose high mortality rate and affecting broiler breast meat quality - Brossi, Camila (2018)
Acute heat stress may affect the quality of broilers meat, however there are no reports considering thermal conditions commercially available in Brazil. In this way, the present work aimed to fill this gap of industrial relevance. Broilers of commercial strain (Cobb 500, n = 540) were randomly assigned to two thermal conditions: acute heat stress (AHS; 35°C; 75 – 85% relative humidity) and not-heat-stress (NS; 22ºC; 83 ± 6.6% relative humidity), for 2 hours prior to slaughter. The mortality rate for AHS broilers reached 37%, which was greater than 5.2% verified for NS. According to the mean values, the broiler chickens were not totally affected in the parameters of pH24h, lightness (L*), cooking loss, and shear force. However, the distributions of data show great variability in the values of pH24h, L* and water holding capacity (WHC) for AHS broilers. It is suggested that AHS broilers, at severe conditions which result in increased mortality, present breast meat with greater incidence of higher pH24h, and lower lightness and WHC values.